2016
DOI: 10.5194/hess-20-1621-2016
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing stream baseflow transit times in tropical montane watersheds

Abstract: Stream water mean transit time (MTT) is a fundamental hydrologic parameter that integrates the distribution of sources, flow paths, and storages present in catchments. However, in the tropics little MTT work has been carried out, despite its usefulness for providing important information on watershed functioning at different spatial scales in (largely) ungauged basins. In particular, very few studies have quantified stream MTTs or have related these to catchment characteristics in tropical montane regions. Her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 47 publications
2
28
0
7
Order By: Relevance
“…It is clear, however, that given the mathematical limitations in representing systems' non-stationarities (Duvert et al, 2016;Seeger and Weiler, 2014), the high temporal resolution of tracer data (Harman, 2015;Heidbüchel et al, 2012), and the general unavailability of long-term tracer records (Hrachowitz et al, 2010;Klaus et al, 2015) required for hydrological modeling under non-stationary conditions, the LCA remains a useful methodology for MTT estimation. This holds true not only in understudied regions such as the tropics (e.g., Farrick and Branfireun, 2015;Muñoz-Villers et al, 2016;Timbe et al, 2014), but also elsewhere (e.g., Duvert et al, 2016;Hu et al, 2015;Seeger and Weiler, 2014).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is clear, however, that given the mathematical limitations in representing systems' non-stationarities (Duvert et al, 2016;Seeger and Weiler, 2014), the high temporal resolution of tracer data (Harman, 2015;Heidbüchel et al, 2012), and the general unavailability of long-term tracer records (Hrachowitz et al, 2010;Klaus et al, 2015) required for hydrological modeling under non-stationary conditions, the LCA remains a useful methodology for MTT estimation. This holds true not only in understudied regions such as the tropics (e.g., Farrick and Branfireun, 2015;Muñoz-Villers et al, 2016;Timbe et al, 2014), but also elsewhere (e.g., Duvert et al, 2016;Hu et al, 2015;Seeger and Weiler, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…Despite the importance of tropical biomes as natural sources and regulators of streamflow, there are very few studies of MTT in tropical environments (e.g., Farrick and Branfireun, 2015;Muñoz-Villers et al, 2016;Roa-García and Weiler, 2010;Timbe et al, 2014). The majority of MTT studies have been conducted in catchments with strong climate seasonality, i.e., located in the Northern and Southern hemispheres (e.g., Lyon et al, 2010;McGlynn and McDonnell, 2003;McGuire et al, 2005), and considerably less attention has been devoted to tropical environments.…”
Section: Introductionmentioning
confidence: 99%
“…Caballero et al (2013) present results from a semidistributed water balance model that indicated that a cloud forest-dominated watershed had greater groundwater recharge than catchments without cloud forest, which resulted in a four-fold greater stream discharge from the cloud forestdominated watershed. In the case of the Los Gavilanes catchment within our Veracruz study, we estimated that the mean stream water residence times across different catchment areas ranged between 1.2 and 2.7 years, which suggests the presence of deep and presumably long subsurface flow paths that contribute to sustain baseflows, particularly during dry periods (Muñoz-Villers et al 2016). Although these findings suggest that the upland areas -which coincide with pine-oak and cloud forests and highest rainfall totals-are the most important for groundwater recharge and downstream discharge, this study did not spatially identify recharge zones or evaluate linkages between PHS payments and recharge zones.…”
Section: Is Mexico's Payments For Hydrologic Services Program Effectimentioning
confidence: 99%
“…such as surface runoff. Evidence from other studies suggests that the role of vegetation cover in water storage and MTT could be suppressed by geomorphology (Timbe et al, 2017) or soil hydraulic properties (Geris et al, 2015;Mueller et al, 2013;Muñoz-Villers et al, 2016). The latter, however, can also be influenced by land use.…”
mentioning
confidence: 97%
“…Transit time also has implications for water quality, since the contact time between water and the soil will affect the chemical composition of the water that finally enters 25 the stream through biogeochemical processes (McGuire and McDonnell, 2006). MTT can be influenced by catchment soil cover (Capell et al, 2012;Rodgers et al, 2005;Soulsby et al, 2006), soil depth, hydraulic conductivity and topographic parameters, such as slope (Heidbüchel et al, 2013;Mosquera et al, 2016b;Muñoz-Villers et al, 2016) or a combination of these factors (Hrachowitz et al, 2009). Changes in vegetation cover and especially soil hydraulic properties as consequence of changes in land management can also modify MTT.…”
Section: Stable Water Isotopes ( 2 Hmentioning
confidence: 99%